Prognostic quality of the Union Internationale Contre le Cancer/American Joint Committee on Cancer TNM classification, 7th edition, for cancer of the maxillary sinus. Issue 3 (20th June 2014) - Kreppel, Matthias; Amir Manawi, Nilofar‐Natalie; Scheer, Martin; Nickenig, Hans‐Joachim; Rothamel, Daniel; Dreiseidler, Timo; Drebber, Uta; Zinser, Max; Zöller, Joachim E.; Guntinas–Lichius, Orlando; Preuss, Simon Florian
Abstract Background Carcinomas of the maxillary sinus are classified according to the Union Internationale Contre le Cancer (UICC)/American Joint Committee on Cancer (AJCC) TNM classification. The purpose of this study was to assess the prognostic significance of the UICC/AJCC TNM classification seventh edition, which was introduced in 2010. Methods One hundred thirteen patients with malignant tumors of the maxillary sinus were included in this study. The prognostic impact of the TNM classification and the UICC/AJCC seventh edition's stage grouping were analyzed in univariate and multivariate analysis. Results The UICC/AJCC stage grouping, the T classification, and the N classification had a significant impact on overall survival (OS) in univariate analysis (p < .05). No significant differences were observed between the groups T4a and T4b (p = .109). In multivariate analysis, the UICC/AJCC stage grouping (p = .031), the N classification (p = .014), and age (p < .001) had a significant impact on OS. Conclusion Although UICC/AJCC stage grouping and the N classification provided a significant prediction of OS in univariate and multivariate analysis, T classification only influenced OS in univariate analysis. © 2014 Wiley Periodicals, Inc. Head Neck 37: 400–406, 2015